DCE-MRI driven 3-D simulations of solid tumour growth - Roque, T; Roque, T; Roque, T (University of Oxford, 2017)
The dataset was used to generate the results presented in the TMI paper 'A DCE-MRI Driven 3D Reaction-DIffusion Model of Solid Tumour Growth'. It includes the script used to generate Figure 2 (along with the data needed for the figures), the simulated and true cell numbers for each time point, and the nifti files for simulated tumours (Cases 1-6 and 10) along with the niftis from true maps for Case 10 (used to generate Fig 3). It also an excel file with the values for the synthetic data analyisis (DICE and volume errors for each of the 15 cases).